CONSEQUENTIALITY BELIEFS AND CONSUMER VALUATION OF EXTRINSIC ATTRIBUTES IN BEEF. (15th August 2017) - LI, XIAOGU; JENSEN, KIMBERLY L.; LAMBERT, DAYTON M.; CLARK, CHRISTOPHER D.
Abstract: This study measures willingness to pay (WTP) for extrinsic attributes (Angus, local, DNA traceable, raised carbon friendly, and humanely treated cattle) in steak and ground beef using choice-based experiments from a national consumer survey. Belief that survey responses could have consequences on beef products offered by the steak and ground beef industry is investigated, as well as its effect on attribute WTP. For most attributes, belief in consequentiality increases WTP. Results suggest that although consequentiality believers tend to place greater importance on certain food industry issues, they are less certain about the attribute's provision actually effecting change in the industry.